Negara Neoliberal, Pembangunan Pariwisata dan Persoalan Kemiskinan di Manggarai Barat, Flores, NTT, Indonesia Timur - Emilianus Yakob Sese Tolo; Maximus Manu; Philipus Ola Daen (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2023)
Neoliberal state policies in many developing countries have led to poverty, environmental problems, and economic inequalities. This article aims to explain the process and mechanism of tourism development in the neoliberal Indonesian state and its impacts on the people of West Manggarai. This research used a qualitative methodology through observation, in-depth interviews and focused group discussions (FGDs). This study argues that tourism development in West Manggarai has been shaped by the intervention of the Indonesian neoliberal state, which tends to side with capital that promotes economic growth. Tourism development in West Manggarai has thus resulted in corruption for the sake of capital accumulation and economic growth. This neoliberal development model has caused poverty, environmental problems, and increased economic inequalities in West Manggarai. However, these negative impacts of tourism development have not yet triggered systematic and progressive civil society movements in West Manggarai. This paper recommends that tourism development in West Manggarai should be carried out in a decentralized manner by emphasizing on the constructive collaboration between different parties, such as local communities, local government, and the central government. The collaboration should be based on the understanding that there is an inseparable relationship between the tourism sector and other sectors, such as agriculture, fisheries, cooperatives, and education.